1998
DOI: 10.1557/jmr.1998.0093
|View full text |Cite
|
Sign up to set email alerts
|

An x-ray photoelectron spectroscopic study of the chemical states of fluorine atoms in calcium silicate glasses

Abstract: X-ray photoelectron spectroscopy has been used to examine the chemical states of fluorine in the glasses of composition xCaF2(50 – x)CaO · 50SiO2 (x = 5, 10, 15, 20, and 25 mol %) and xCaF2(50 – x/2)CaO(50 – x/2)SiO2 (x = 5, 10, 15, and 20 mol %). The analysis of the F1s spectra indicated that Ca2+ and F- ions introduced as CaF2 are favorably located among the Si–O skeleton forming Ca–F clusters. The fraction of the bridging and nonbridging oxygen atoms was derived from the O1s spectra, and the network of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 14 publications
4
25
0
1
Order By: Relevance
“…The binding energies are close to that of CaF 2 crystal (684.3 eV, 13) 685.1 eV 20) ) rather than that of F-containing VAD SiO 2 glass (687.1 eV). 13) It has been reported that the fluorine in the VAD SiO 2 glass form covalent Si-F bonds. 21) Consequently, it can be concluded that the fluorine is dominantly coordinated with Ca 2ϩ in the present composition ranges of the CaO-SiO 2 -CaF 2 and CaO-SiO 2 -CaF 2 -FeO x glasses.…”
Section: Figmentioning
confidence: 63%
See 4 more Smart Citations
“…The binding energies are close to that of CaF 2 crystal (684.3 eV, 13) 685.1 eV 20) ) rather than that of F-containing VAD SiO 2 glass (687.1 eV). 13) It has been reported that the fluorine in the VAD SiO 2 glass form covalent Si-F bonds. 21) Consequently, it can be concluded that the fluorine is dominantly coordinated with Ca 2ϩ in the present composition ranges of the CaO-SiO 2 -CaF 2 and CaO-SiO 2 -CaF 2 -FeO x glasses.…”
Section: Figmentioning
confidence: 63%
“…tion of the F1s XPS spectra range from 683.4 to 684.9 eV. The binding energies are close to that of CaF 2 crystal (684.3 eV, 13) 685.1 eV 20) ) rather than that of F-containing VAD SiO 2 glass (687.1 eV). 13) It has been reported that the fluorine in the VAD SiO 2 glass form covalent Si-F bonds.…”
Section: Figmentioning
confidence: 68%
See 3 more Smart Citations